PENGEMBANGAN PASAR TRADISIONAL SONGGOLANGIT PONOROGO: TINJAUAN PERSPEKTI EKONOMI ISLAM - AHMAD LUKMAN NUGRAHA; MECHIO LESMANA; ROYYAN RAMDHANI DJAYUSMAN (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2019)
This study aims to analyze traditional market development Songgolangit Ponorogo from an Islamic economic perspective. This study used a qualitative method. Qualitative methods are used to analyze the role of traditional market development from the perspective of Islamic Economics. Including data tecnic by copersition, dokumentation, and Focus Group Discossion. The results of this study indicate that the management of the Songgolangit market is good. Development of the Ponorogo Songgolangit traditional market through the stages of planning, organizing, field action, supervision and evaluation. Market development in Islamic perspectives includes price monitoring, fraud control, general supervision, quality control and halal goods, control of stockpiling, and control of prohibited transactions. Local governments play an important role in supervision and need to work together with the MUI in forming